Biodegradation of aged composition of polyethylene with synthetic polyester - Łabużek, S.; Nowak, B.; Pająk, J. (Polimery, 2022)
The effect of preliminary aging, in abiotic conditions (photo-, thermal or photo-thermal degradation), of the film made of 80 % of PE-LD and 20 % of polyester "Bionolle®" on the course of biodegradation caused by Penicillium funiculosum (filamentous fungi) was investigated. The films made of single components of this mixture (Table 1) were also investigated to compare the results obtained. The degrees of each kind of degradation have been estimated on the basis of changes of film weight loss (Table 2 and 3), the mechanical properties (Table 4) and morphology of the surface (characterized using scanning electron microscopy, Fig. 1 and 2). Changes in chemical structure of polyethylene/polyester blend caused by degradation were interpreted on the basis of IR spectra analysis (Fig. 3-5). It was found that abiotic degradation of the polymers accelerated their subsequent biodegradation and that addition of "Bionolle®" polyester made PE-LD more sensitive to degradation processes.